Análise numérica de painéis pré-moldados de fechamento em edificações de pequena altura - Freitas, Harisson Silva de (2012)
Abstract: The civil construction has intensified efforts in the search and implementation of strategies for the modernization of the sector, in which the rationalization of constructive processes has a crucial role. The most notable trends are related to employment of systems, wholly or partly pre-fabricated, able to maximize the potential of rationalization of enforcement proceedings. The use of streamlined systems of closing such as precast panels allows combining rationalization at the speed of construction of the fence subsystem. In this context, this study aims to analyze some important problems arising from the use of precast panels of closing in small height buildings or until 3 floors, application that has becoming very common in the country. The elements of analysis are types of link panelstructure for gravity and bracing, thermal effects on the panels and the placement of dilatation joints. Numerical analyzes are developed using the ANSYS computer program for the modeling of the problem considering solid elements. The physical nonlinear behavior of materials involved is considered in the simulations, as well as the possibility of considering the effect of contact between the surfaces of the panels. The analyses show that the proximity between the panels should be carefully defined to avoid contact stresses resulting from thermal effects or expansion joints not provided or improperly arranged.